THE EFFECT OF TRANSITION-ACTION-DETAILS (TAD) STRATEGY ON THE WRITING ABILITY ON RECOUNT TEXT OF THE SECOND YEAR STUDENTS OF SMPN 1 SUNGAI APIT, SIAK REGENCY - Riatie, Nolanda; Dahnilsyah, Dahnilsyah; Marzuki, Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to investigate the effectiveness of usingTransition Action Details Strategy to teach writing recount texts to the second yearstudents of â€œSMPN 1 Sungai Apit, Siak Regencyâ€ in Academic Year 2018/2019. Thisresearch was a pre experimental research with one group pre-test and post-test design.The sample of this research was VIII.I which consisted of 26 students. The technique ofdata collecting is measurement, the tool of which a written tests. The mean score of pretestwas 61.40 and the mean score of post-test was 68.53. The data calculation showedthat the value of t-test was -1.672. The values of t table on the df (degree of freedom) 25is 2.060 with the level significance (Î±)=5%. Then, the t-test was large than the t-tableon significant level 5%. The level significance was -1.672 < 2.060. Thus, teachingwriting ability recount texts using TAD strategy to the second year students of â€œSMPN 1Sungai Apit, Siak Regencyâ€ in Academic Year 2018/2019 could be categorized as â€œnoeffectâ€.Key Words: Transition Action Details Strategy, Recount Texts